Det oversete argument - Ravn, Martin (Dansk Teologisk Tidsskrift, 2012)
The article presents American semiotician Charles Sanders Peirce’s 1908 essay “The Neglected Argument for the Reality of God” which has been viewed as notoriously difficult and obscure. The article is primarily concerned with giving an account of the three stages that constitute Peirce’s argument, as well as giving an interpretation of their interrelation (a much discussed problem in Peirce scholarship). Conclusively, the article reviews the relevance of the theological views presented in Peirce’s argument by sketching how Peirce’s idea of God draws the current discussion of the relationship between methodological naturalism